Shadow Play #2 - Rivera, Richard (Scout Comics, 2021)
Set in the Stabbity Bunny universe! Joy and Bard are in the Shadow Realm with no plan and zero allies. Their prospects change quickly when they encounter a powerful creature that can provide help, so long as they stay on his good, non-murderous, side. In a nearby village a secret society offers aid against the Shadow King as long the duo is willing to work with them. The Stabbity Bunny world expands with concepts created by Richard Rivera and Alex Lobato.